Nitrosporeusine analogue ameliorates Chandipura virus induced inflammatory response in CNS via NF kappa b inactivation in microglia - Verma, Abhishek Kumar; Waghmare, Trushnal S.; Jachak, Gorakhnath R.; Philkhana, Satish Chandra; Reddy, D. Srinivasa; Basu, Anirban (PLOS Neglected Tropical Diseases, 2018)
Chandipura Virus (CHPV), a negative-stranded RNA virus belonging to the Rhabdoviridae family, has been previously reported to bring neuronal apoptosis by activating several factors leading to neurodegeneration. Following virus infection of the central nervous system, microglia, the ontogenetic and functional equivalents of macrophages in somatic tissues gets activated and starts secreting chemokines, thereby recruiting peripheral leukocytes into the brain parenchyma. In the present study, we have systemically examined the effect of CHPV on microglia and the activation of cellular signalling pathways leading to chemokine expression upon CHPV infection. Protein and mRNA expression profiles of chemokine genes revealed that CHPV infection strongly induces the expression of CXC chemokine ligand 10 (CXCL10) and CC chemokine ligand 5 (CCL5) in microglia. CHPV infection triggered the activation of signalling pathways mediated by mitogen-activated protein kinases, including p38, JNK 1 and 2, and nuclear factor kappa B (NF-kappaB). CHPV-induced expression of CXCL10 and CCL5 was achieved by the activation of p38 and NF-kappaB pathways. Considering the important role of inflammation in neurodegeneration, we have targeted NF-kappaB using a newly synthesised natural product nitrosporeusine analogue and showed incapability of microglial supernatant of inducing apoptosis in neurons after treatment.